Kompetensi Guru dalam Menerapkan Merdeka Belajar di Sekolah Dasar - Wulida Arina Najwa; Slamet Widodo; M. Misbachul Huda; Adhy Putri Rilianti; Wahyu Nugroho (PGSD FKIP UPR, 2023)
As an effort by the Ministry of Education and Culture to improve the quality of human resources, an independent learning policy was made. The quality of Indonesian human resources is still a challenge to solve because the results of surveys from international institutions such as PISA (Program for International Student Assessment) and TIMSS (Trend in International Mathematics and Science Study) still show a protruding ranking. In independent learning there are four main policies, namely (1) freedom of student assessment, (2) national exams replaced by AKM (Minimum Competency Assessment) and character surveys, (3) RPP (Learning Implementation Plan) one sheet, and (4) PPDB system (New Student Admissions) zoning. Therefore, to increase the success of implementing independent learning, it is necessary to have the ability of teachers in the teaching process which results in an independent student learning process. This article uses the literature review method to assess the teacher's abilities. The data collection method uses analysis of data sources obtained from various forms such as journal articles, books, Ministry of Education and Culture policies, and statutory documents. The results of this study indicate that to implement independent learning teachers must master pedagogical skills, skills to adapt teaching styles to student learning styles, skills to master online learning, and skills to master learning strategies. In addition, teachers must also master the principles of independent learning, forms of independent learning, and student learning activities.